(untitled) (Coordinates of Public Administration, 2026)
The article, based on an analysis of the real state of affairs in Ukraine, caused by the introduction of the legal regime of martial law on February 24, 2022 and the beginning of the full-scale Russian-Ukrainian war, which has lasted almost four years, shows the regulatory and legal framework regarding the possibility of holding (not holding) local elections, that long before the legally established date for local elections (October 26, 2025), the problem of the need and real possibility of holding them under the legal regime of martial law was actively discussed in Ukrainian society; it was found that, according to current legislation, the principle of continuity of power operates in Ukraine. The President, the Verkhovna Rada of Ukraine, village, settlement, city, district, district councils in cities (if they are established), regional councils, village, settlement and city mayors shall act until the swearing-in of the newly elected members — the President, parliamentarians, deputies of local councils of all levels and village, settlement and city mayors; it has been proven that the President of Ukraine, the people’s deputies, the associations of local councils, and the vast majority of representatives of political parties and public figures have reached the only correct decision about the impossibility of holding local elections at this time. The adoption by the parliament of the relevant resolution on October 8, 2025, became a political act on the part of the Verkhovna Rada of Ukraine in support of the initiative of the vast majority of institutions and representatives of civil society to that all local self-government remains legitimate and functioning after the end of five years of office (October 25, 2025); It is confirmed that local councils of all levels and village, settlement, and city mayors elected in accordance with the Law of October 25, 2020 are authorized, except for those whose powers have been terminated early in the manner established by the Law, until the next elections are held after the abolition or termination of the legal regime of martial law.